Uso da rutina como atenuador do estresse salino no cultivo do pimentão amarelo em ambiente protegido - Lopes, Francisca Gleiciane Nascimento (2023)
Peppers (Capsicum annuum L.) are one of the main vegetables produced in the world and are among the most commercialized and consumed in Brazil, due to the ease of cultivation in small areas, their short cycle and their high economic value. And, given the need for many farmers to use lower quality water for irrigation, it is necessary for researchers to study methods and products that can mitigate the harmful effects of salinity on plants, such as the biostimulant rutin, which has been widely used in pharmaceutical industry as vitamin P for humans. Therefore, research was carried out in the municipality of São Benedito-CE, seeking to evaluate whether the application of the biostimulant rutin mitigates the harmful effects of salinity on yellow pepper cultivation, grown under a protected environment. The experimental design used was randomized blocks, in a split-plot scheme (4 x 4), with four replications. The plots consisted of four levels of electrical conductivity of irrigation water (0.3; 1.5; 3.0 and 4.5 dS m-1) and the subplots consisted of four dosages of the biostimulant rutin (0.0; 6.0, 12.0 and 18.0 g L-1) applied via foliar spray. Analyzes were made of growth variables (plant height, stem diameter and dry weight of the aerial part), production, post harvest fruit (length, transversal and longitudinal diameters and average fruit weight, number of fruits per plant , productivity and soluble solids content) and the capture of thermometric images to measure canopy temperatures. Data for each observed variable were subjected to analysis of variance. The dosages of the biostimulant rutin did not attenuate the effects of salts on plants in any of the variables analyzed. The higher levels of electrical conductivity of irrigation water caused a marked reduction in the growth variables of plant height, stem diameter and dry weight of the shoot. The post-harvest variables, except for the soluble solids content, showed decreases with the increase in the electrical conductivity of the irrigation water. Canopy temperature increased with increasing salinity levels of irrigation water. There was thermal variability in the canopy between the image capture times, which must be related to the irrigation schedule and the small thermal amplitude inside the protected environment.